Penggunaan Elaboration Likelihood Model Dalam Menganalisis Penerimaan Teknologi Informasi - vitrian, vitrian2 (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2010)
This article discusses some technology acceptance models in an organization. Thorough analysis of how technology is acceptable  help managers  make any planning to implement new teachnology and make sure that new technology could enhance  organization’s performance. Elaboration Likelihood Model (ELM) is the one which sheds light on some behavioral factors in acceptance of information technology. The basic tenet of ELM states that human behavior in principle can be influenced through central route and peripheral route. The use of central route and peripheral route could be adapted to individual condititon in an organization so as to appropriate route selection could accomplish the goals of information technology application. Keywords: information technology, Elaboration Likelihood Model, acceptance level